Evaluation of Drainage Channel Capacity along Kolonel Sugiono Street, Waru District, Sidoarjo Regency - Puspasari, Aisyah Dwi; Ramadhan, Muhammad Lucky; Hendrawan, Ilham Mars; Winata, Dyas Ray; Ardhani, Muhammad Zidan; Prayoga, Rahmat Budi; Fabiantoro, Alif Reza (Faculty of Civil Engeneering and Planning - ITATS, 2025)
Urban drainage systems in rapidly developing areas often experience reduced performance due to increased surface runoff, resulting in frequent waterlogging. This study evaluates the hydraulic capacity and performance of the existing drainage channel along Kolonel Sugiono Street, Waru District, Sidoarjo Regency, where inundation depths of approximately 15–40 cm are commonly observed during rainfall events. Hydrological analysis was conducted using annual maximum daily rainfall data from the Juanda Meteorological Station for the period 2015–2024. Design rainfall was estimated using the Gumbel extreme value distribution with a 5-year return period and a 90% confidence level, followed by rainfall intensity calculation using the Mononobe method. The design flood discharge was then determined using the Rational Method for a 6.25-ha urban catchment area. Hydraulic analysis employing Manning’s equation was performed to evaluate the capacity of the existing drainage channel based on field-measured dimensions. The results show that the design flood discharge is approximately 1.168 m³/s, while the capacity of the existing channel is only 0.293 m³/s, indicating that the channel is hydraulically inadequate. To address this condition, a channel redesign based on the economic cross-section principle was proposed, resulting in increased channel dimensions and the inclusion of a freeboard. The redesigned channel is capable of conveying a discharge of 1.258 m³/s, exceeding the design requirement. These findings provide a technical basis for improving drainage performance and mitigating flooding in the study area